Report of two cases and a systematic review of breast cancer with gastrointestinal metastasis - Zhong, Chenhan; Fang, Xuefeng; Zhu, Lizhen; Li, Dan; Tang, Jinlong; Yuan, Ying (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Zhong C, Fang X, Zhu L, Li D, Tang J, Yuan Y. Report of two cases and a systematic review of breast cancer with gastrointestinal metastasis. Turk J Gastroenterol 2019; 30(11): 997-1000.